Menopause symptoms in women and its relation with using complementary and alternative medicines: A survey in southeast Iran - Dehghan, Mahlagha; Isari, Zahra; Abbaszadeh, Mohammad Hossein; Ghonchehpour, Asma (Frontiers in Public Health, 2022)
Background: Postmenopausal women are interested in using complementary and alternative medicine because of the menopausal symptoms, and the side effects of chemical medications and hormone therapy. Therefore, this study aimed to investigate the relationship between the use of complementary medicine and menopausal symptoms among postmenopausal women. Methods: This descriptive-analytical study was conducted on 288 postmenopausal women, who referred to health centers in Kerman, southeastern Iran, in 2020-2021. Data were collected using demographic questionnaire, the CAM questionnaire, and the Menopause Rating Scale (MRS). Results: The mean score for the menopausal symptoms of the participants was 8.73 ± 6.11. Only 28.8% of the participants had no/little symptoms. Sixty-five-point three percent of the participants used at least one type of Complementary and Alternative Medicine in the previous year. The most commonly used types of complementary and alternative medicines were nutritional supplements, prayer, and medicinal herbs. A significant association was found between the use of medicinal herbs, dry cupping, relaxation and meditation, prayer, and menopausal symptoms. Women experiencing menopausal symptoms used more CAM methods than those without menopausal symptoms (Odds ratio = 2.25, 95% confidence interval = 1.33 – 3.80). Conclusion: According to the study results, further research in different communities with different health systems is recommended to investigate the relationship between complementary and alternative medicine and menopausal symptoms among women.